Sensory quality of custard tart as affected by varying levels of Mabolo (Dispyros blancoi A. DC) Flesh - Baclayon, Loraine P.; Cerna, Julious B.; Cimafranca, Lynette C. (Annals of Tropical Research, 2020)
Mabolo (Diospyros blancoi A. DC) is an underutilized fruit in the Philippines. To add value and maximize the utilization of this nutritional fruit, the potential of mabolo for the production of highly saleable baked products, such as tarts, was explored. Specifically, the study aimed to formulate a custard tan filling with mabolo flesh as a flavorant using a single factor experiment arranged in a Completely Randomized Design (CRD). Six levels of mabolo flesh (0, 15, 30, 45, 60, & 75% w/w) were used. The sensory attributes for color, taste, aroma, texture, flavor, and general acceptability, were evaluated. The optimum formulation of the tart filling was determined using Regression analysis. Results showed that mabolo custard tart filling had yellowish-brown to brown color, moderately sweet to sweet taste, and soft to slightly fibrous texture. The mabolo fruit aroma and flavor in the tarts ranged from having none to perceptible. The Analysis of Variance revealed that different levels of mabolo flesh cause a significant effect on the color (p<0.01). The optimum formulation and the recommended level of mabolo flesh in custard tart filling production was 80.54% w/w.